Bioaccumulation of heavy metals, metalloids, and chlorine in ectomycorrhizae from smelter-polluted area - Cejpková, Jaroslava; Gryndler, Milan; Hršelová, Hana; Kotrba, Pavel; Řanda, Zdeněk; Synková, Iva; Borovička, Jan (Environmental pollution (Barking, Essex, 2016)
Ectomycorrhizal (ECM) fungi contribute to the survival of host trees on metal-rich soils by reducing the transfer of toxic metals into roots. However, little is known about the ability of ECM fungi to accumulate elements in ectomycorrhizae (ECMs). Here we report Ag, As, Cd, Cl, Cu, Sb, V, and Zn contents in wild-grown Norway spruce ECMs collected in a smelter-polluted area at Lhota near Příbram, Czech Republic. The ECMs data were compared with the element concentrations determined in the corresponding non-mycorrhizal fine roots, soils, and soil extracts. Bioaccumulation factors were calculated to differentiate the element accumulation ability of ECMs inhabited by different mycobionts, which were identified by ITS rDNA sequencing. Among the target elements, the highest contents were observed for Ag, Cl, Cd, and Zn; Imleria badia ECMs showed the highest capability to accumulate these elements. ECMs of Amanita muscaria, but not of other species, accumulated V. The analysis of the proportions of I. badia and A. muscaria mycelia in ECMs by using species-specific quantitative real-time PCR revealed variable extent of the colonization of roots, with median values close to 5% (w/w). Calculated Ag, Cd, Zn and Cl concentrations in the mycelium of I. badia ECMs were 1 680, 1 510, 2 670, and 37,100 mg kg-1 dry weight, respectively, indicating substantial element accumulation capacity of hyphae of this species in ECMs. Our data strengthen the idea of an active role of ECM fungi in soil-fungal-plant interactions in polluted environments.
Keywords: mycelium; Mycorrhizae; Silver; Ectomycorrhiza; těžké kovy; Česká republika; Plant Roots; látky znečišťující půdu; Metalloids; polokovy; Soil; Soil Pollutants; Roots; kořeny rostlin; Czech Republic; Quantitative real-time PCR; Mycelium; chlor; Ectomycorrhizal fungi; Metals, Heavy; Chlorine; mykorhiza; Cadmium